ANALISIS KARAKTERISTIK DAN KEBUTUHAN PARKIR DI PASAR KRENENG - Jaya Wikrama, A.A. (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010)
Kreneng Market is one of traditional markets in Denpasar City with high activities where during peak hours many vehicles find difficulties to search for parking lot. The objectives of this study were to analyse parking characteristics and demand. Result of parking characteristics analyses were as follows: for off street parking, the highest parking volume was for motor cycle (2,768 vehicles). The highest average parking duration was for motor cycle (1,953 hour/vehicle). The highest parking accumulation was 473 vehicles/hour between 05.00-06.00 am. The highest parking capacity was for motor cycle (171 vehicles/hour). Highest Parking Index was 2.8. For on street parking, the highest parking volume was for motor cycle (782 vehicles) on Rijasa St. The highest average parking duration was for light vehicle (2.340 hour/vehicle) on Kamboja St. The highest parking accumulation was for motor cycle (220 vehicles/hour) on Rijasa St between 05.00- 06.00 am. Highest parking capacity was for motor cycle (57 vehicles/hour) on Rijasa St. Highest parking index was for motor cycle (3.86) on Rijasa St. Parking stall required for off-street parking were: 618 stalls for motor cycles and 67 stalls for light vehicles. For on street parking: 41 stalls of light vehicle on Kamboja St, 82 motor cycle stalls and 42 light vehicle stalls on Rampai St, 182 motor cycle stalls and 34 light vehicle stalls on Rijasa St.
Keywords: Parking characteristics, demand, Kreneng Market